Weathering pits as a geochronometer of environmental changes in the State of Pernambuco, Northeastern Brazil. (10th March 2023) - Gomes da Silva Listo, Danielle; Francisca Tavares de Melo Balder, Rhaissa; Carlos de Barros Corrêa, Antonio; Albuquerque Meira Coelho Ramos, Débora; Calegari, Marcia Regina
Abstract: This research was intended to interpret, by means of several empirical bases, the quaternary climate variabilities in the area of Fazenda Nova. The premise that guides the investigation is that the sedimentary fills of the weathering pits favors the understanding of the landscape and geomorphological changes in the area, by means of the investigation of a depositional environment that is still closely linked to the current landscape. Due to that, the analysis of the depositional events and climate variabilities was done based on a morphostratigraphic approach, dating by Optically Simulated Luminescence (LOE), O 18 isotope of carbonatic crust and phytolith analysis. The results showed that the deposits that fill the weathering pits were derived from gravitational sedimentation of the debris flow type, under torrential conditions, evidencing that the genesis of these records was associated with cycles of pedogenesis/morphogenesis under several combinations of semiaridity at work in the area.